Myths and realities of crime and justice: what every American should know - Barkan, Steven E. (Jones and Bartlett Publishers, 2008)
What no one is telling you about crime and justice -- The crime problem -- How much crime is there and who commits it? -- Robbers, rapists, and serial killers: violent crime in America -- Hookers, dopers, and corporate crooks: economic, exploitive, and consensual crime -- Victims and victimization: will you be next? -- Crime and criminal law: order, liberty, and justice for all? -- Why they break the law -- Taking it to the streets: cops on the job -- Pre-trial procedures and plea bargaining: from arrest to "let's make a deal" -- Criminal trials and courtroom issues: convicting the innocent, exonerating the guilty -- Prisons and jails: punishment at any cost? -- Community corrections and juvenile justice -- Conclusion: what every American should know